Anomalous Evolution of Strength and Microstructure of High‐Entropy Alloy CoCrFeNiMn after High‐Pressure Torsion at 300 and 77 K. Issue 1 (6th November 2019) - Podolskiy, Aleksey V.; Shapovalov, Yuriy O.; Tabachnikova, Elena D.; Tortika, Aleksandr S.; Tikhonovsky, Mikhail A.; Joni, Bertalan; Ódor, Eva; Ungar, Tamas; Maier, Stefan; Rentenberger, Christian; Zehetbauer, Michael J.; Schafler, Erhard
Abstract : Ultrafine and nanocrystalline states of equiatomic face‐centered cubic (fcc) high‐entropy alloy (HEA) CoCrFeNiMn ("Cantor" alloy) are achieved by high‐pressure torsion (HPT) at 300 K (room temperature, RT) and 77 K (cryo). Although the hardness after RT‐HPT reaches exceptionally high values, those from cryo‐HPT are distinctly lower, at least when the torsional strain lies beyond γ  = 25. The values are stable even during long‐time storage at ambient temperature. A similar paradoxal result is reflected by torque data measured in situ during HPT processing. The reasons for this paradox are attributed to the enhanced hydrostatic pressure, cryogenic temperature, and especially large shear strains achieved by the cryo‐HPT. At these conditions, selected area electron diffraction (SAD) patterns indicate that a partial local phase change from fcc to hexagonal close‐packed (hcp) structure occurs, which results in a highly heterogeneous structure. This heterogeneity is accompanied by both an increase in average grain size and especially a strong decrease in average dislocation density, which is estimated to mainly cause the paradox low strength. Abstract : Ultrafine and nanocrystalline states of high‐entropy alloy CoCrFeNiMn ("Cantor") achieved by high‐pressure torsion (HPT) at 77 K exhibit strength values being distinctly lower than those achieved by HPT at 300 K. The strength drop is attributed to distinct decreases/increases of dislocation density and crystallite size, respectively, whereas the lattice partially changes from fcc to hcp structure.